Investigating the impact of quarantine on mental health: insights from the COVID-19 international border surveillance study in Canada. Issue 5 (5th September 2021) - Regehr, Cheryl; Goel, Vivek; De Prophetis, Eric; Jamil, Munaza; Mertz, Dominik; Rosella, Laura C.; Bulir, David; Smieja, Marek
Abstract : Background: Nations throughout the world are imposing mandatory quarantine on those entering the country. Although such measures may be effective in reducing the importation of COVID-19, the mental health implications remain unclear. Aims: This study sought to assess mental well-being and factors associated with changes in mental health in individuals subject to mandatory quarantine following travel. Method: Travellers arriving at a large, urban international airport completed online questionnaires on arrival and days 7 and 14 of mandated quarantine. Questionnaire items, such as travel history, mental health, attitudes toward COVID-19, and protection behaviours, were drawn from the World Health Organization Survey Tool for COVID-19. Results: There was a clinically significant decline in mental health over the course of quarantine among the 10 965 eligible participants. Poor mental health was reported by 5.1% of participants on arrival and 26% on day 7 of quarantine. Factors associated with a greater decline in mental health were younger age, female gender, negative views toward quarantine measures and engaging in fewer COVID-19 prevention behaviours. For instance, travellers who stated that they rarely wore masks had nearly three times higher odds of developing poor mental health. Conclusions: Although the widespread use of quarantine may be effective in limiting the spread of COVID-19, the mental health implications are profound and have largely been ignored in policy decisions. Psychiatry has a role to play in contributing to the public policy debate to ensure that all aspects of health and well-being are reflected in decisions to isolate people from others.